Mapping hot-pressed Li6.25Al0.25La3Zr2O12 (LLZO) grains and grain boundaries through a simple thermal grooving technique. Issue 3 (2nd July 2020) - Sato, Masumi; Garcia-Mendez, Regina; Sakamoto, Jeff
ABSTRACT: Li6.25 Al0.25 La3 Zr2 O12 (LLZO) is one of the most promising solid-state electrolytes due to its electrochemical and chemical stability against metallic Li and high ionic conductivity at room temperature. Despite its favorable attributes, it has been shown that Li metal can penetrate LLZO above a critical current density (CCD). Currently, the mechanism by which this phenomenon occurs has not been completely elucidated. However, microstructural defects such as grain boundaries have been pointed out as one of the defects where Li metal preferentially propagates. Thus, microstructural characterization techniques that do not require extensive sample preparation are valuable to correlate processing conditions with resulting microstructure and properties. In this work, a thermal grooving process was optimized to minimize lithium loss allowing to visualize and study the microstructure of LLZO. The proposed technique does not require extensive sample preparation such as what is required for electron backscattering diffraction (EBSD). Variables such as temperature and atmosphere were tuned to optimize thermal grooving while maintaining phase purity (91.4 wt %). We believe this simple method to visualize grains and grain boundaries will help guide efforts to correlate processing conditions with electrolyte properties and ultimately move forward to enable solid-state battery technology.